MUST ONCOLOGICAL PRINCIPLES BE IN THE SURGERY OF MENINGIOMAS? EN BLOC REMOVAL OF GIANT RIGHT FRONTAL MENINGIOMA WITH EXTRACRANIAL SPREAD. DESCRIPTION OF A CLINICAL CASE - V. B. Karakhan; V. A. Aleshin; D. M. Belov; N. V. Sevyan; D. K. Stelmakh; A. V. Zotov (Опухоли головы и шеи, 2015)
The use of the oncological principle – en bloc ablastic tumor resection – can expect a breakthrough in the treatment of baseline unfavorable patient groups. In the described case of atypical meningioma, its en bloc resection presents significant technical difficulties when accomplishing the task associated with the giant sizes of a tumor as an iceberg growing outside and into the cranial cavity, its rich vascularization from both the internal and external carotid artery system, with the involvement of the superior sagittal sinus, the presence of a dense bone crown that combines the three-component construction of a neoplasm, which made difficult safe mobilization and scanning in the cranial cavity.In such topographic variants, the criteria for the Simpson radical meningioma resection are inapplicable and only en bloc tumor resection may reflect the oncological principles of surgery. The technologies of en bloc resection of intracranial meningiomas should be more frequently used because preoperative neurovisualization and even histological diagnosis does not always allow the grade of meningiomas to be specified.